Effects of excessive nitrogen fertilizer and soil moisture deficiency on antioxidant enzyme system and osmotic adjustment in tomato seedlings - Zhang, Yujie; Yu, Shuangen; Li, Zijia; Chang, Tingting; Xu, Qicong; Xu, Huilian; Zhang, Jie (International Journal of Agricultural and Biological Engineering, 2022)
Long-term excessive application of nitrogen fertilizer induces secondary salinization of soil, which results in inhibiting plant growth. In addition, soil moisture deficiency also affects plant growth. To investigate the effects of excessive nitrogen fertilizer and soil moisture deficiency on the antioxidant enzyme system, plant water relations analyzed through pressure-volume (P-V) curve, and photosynthetic light response parameters in tomato (Solanum lycopersicum L. Myoko) seedlings, an indoor experiment of about 50 d was conducted using two irrigation water amounts based on field capacity (soil moisture deficiency: 50%-80%; adequate water: 70%-80%), two nitrogen fertilizer rates (moderate nitrogen; excessive nitrogen fertilizer: 0.585 g/pot) and two types of irrigation water (tap water and microbial diluent). The results showed that excessive nitrogen fertilizer (N) and soil moisture deficiency (W) reduced the biomass of tomato seedlings. In comparison to CK (combination of adequate water and tap water quality), microbial dilution (EM) increased plant biomass by 5.2%. Also, the nitrogen application increased chlorophyll relative contents (SPAD). The maximum net photosynthetic rate (Pc) decreased with nitrogen application and increased with EM application and irrigation amount. Excessive nitrogen application increased the plant nitrate reductase activity (NR). The plant NR in the N treatment showed a 13.0% increase compared to CK, and the plant NR in the treatment of nitrogen application with water deficiency (WN) increased 34.0% compared to water deficiency (W). After applying excessive nitrogen, N, EM-N, WN, EM-WN respectively increased the plant nitrate reductase activity by 13.0%, 22.9%, 34.0%, and 28.6%, compared with the corresponding treatment with moderate nitrogen (i.e., CK, EM, W and EM-W). In addition, the activities of antioxidant enzymes [superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT)] in four treatments of nitrogen application (N, EM-N, WN, EM-WN) also increased significantly. Both soil moisture and nitrogen fertilizer significantly affect the parameters of osmotic adjustment, which is manifested in the reduction of osmotic potential (πFT), and the increase in the osmotic concentration (Cosm) and concentration difference (ΔCosm). But the decrease in the relative water content of apoplast (ζap) indicated that water deficiency and excessive nitrogen reduced the water absorption and water retention capacity of tomatoes to a certain extent. In conclusion, excessive nitrogen application and soil moisture deficiency inhibit plant growth significantly in this experiment. Meanwhile, microbial dilution can alleviate excessive nitrogen fertilizer and water stress to some extent, but the effect was not significant.Keywords: antioxidant enzyme, nitrogen, osmotic adjustment, pressure-volume curve, stress, tomato, waterDOI: 10.25165/j.ijabe.20221502.5555Citation: Zhang Y J, Yu S E, Li Z J, Chang T T, Xu Q C, Xu H L, et al. Effects of excessive nitrogen fertilizer and soil moisture deficiency on antioxidant enzyme system and osmotic adjustment in tomato seedlings. Int J Agric & Biol Eng, 2022; 15(2): 127–134.